Analysis of Combination of Natural Fiber Bamboo and Rattan Fiber for Alternative Material in Ship Hull - Putri Ananda, Deas (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
The growing public awareness of the environmental atmosphere has triggered a paradigm shift to design composite materials that are environmentally friendly and energy efficient. Composite materials made from natural fibers have been able to replace metal, steel, and wood because of their ease of use and features. Indonesia has a lot of natural fiber potential, one of which is rattan and bamboo fiber which has significant potential for composites. The use of bamboo and rattan fibers as reinforcement in composite materials has increased rapidly and has undergone a high-tech revolution in recent years in response to the increasing demand to develop biodegradable, sustainable and recyclable materials. In this research, a test made from natural fibers was carried out to find out whether the composite was suitable for use as a substitute for fiberglass on ship hulls. The results of the Tensile test for composites reinforced with natural fibers of bamboo and rattan fiber in the 90° fiber direction obtained the average value of the three experiments with a value of 67,41 Mpa and in the 45° fiber direction the average value of the three experiments was obtained with a value of 57,67 Mpa. The results of the bending test for composites reinforced with natural fibers of bamboo and rattan fiber in the 90° fiber direction obtained an average value of the three experiments with a value of 114,64 Mpa and Dan in the 45° fiber direction obtained an average value of the three experiments with a value of 129,93 Mpa.